Energy-Saving Potential of Daylighting in the Atria of Colleges in Najran University, Saudi Arabia (International Journal of Built Environment and Sustainability, 2019)
Daylighting is recognised as an effective strategy for enhancing visual comfort and reducing energy used for electric lighting. Najran University, Saudi Arabia, has 15 colleges for males and 10 colleges for females. Each college has several atria and courtyards for introducing daylighting into the hearts of college buildings. However, the electrical lights used in the colleges atria and linked corridors keep on all the daytime. This study is an attempt to investigate the daylight illuminance level and energy-saving potential on the atria and linked corridors when it incorporates a time-scheduling lighting control system. The field measurements were performed in the College of Applied Medical Sciences. The results indicate that daylight illuminance in the atrium spaces are abundant with an average illumination level on the atrium floor varying from 300 lux to 3 600 lux, depending on the time of the day. In the clear sky climate of Najran city throughout the year, the time-scheduling control system is effective and found to contribute to approximately 43 855.2 kWh of annual energy savings in electrical-lighting consumption in the present case study scenario. The total annual energy savings from all 25 colleges at Najran University is 1 096 380 kWh/year, which results in a cost saving of approximately 93,512.86 USD. There would be additional substantial savings from other atria and courtyards in all of the college buildings throughout the campus
Keywords: Building atrium; Case study; Daylight illuminance; Clear sky; Energy saving; Lighting control.